????? ?? ????? ??????? ? ????????? ?? ????? ?????????? : AN NAHT IN ARABIC LANGUAGE AND ABREVIASI IN INDONESIAN LANGUAGE - Rita Gamasari (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2020)
Abstract: As for the main issue in this research, what is the object of the agreement and the difference between sculpture in Arabic and Abreviasi in Indonesian language? As for sculpting in the Arabic language, it is called abbreviation, it is the abbreviation of one or more words. The term carving in the Indonesian language is called Abreviasi. At the time of the hadith, the language needs sculpting and abreviasi to shorten speech and make it easier to pronounce. This research is very important for the research, especially for students of the Arabic Language Department. If they do not understand the sculpture well, it is difficult for them to understand the carved words and translate them into the Indonesian language well. As well as abreviasi in the Indonesian language and it is a phenomenon of linguistic that has expanded its use recently. This research is a desk-to-desk search. The research makes the agreement and the difference between sculpture in Arabic and abreviasi in the Indonesian language in terms of concept. As for the agreement in terms of the three types, and its difference is four. The agreement in terms of roads is seven, and the difference between them is eight. ??????? ????????: ?????? ????? ???????